Strategy communication effectiveness in the South African banking industry. - Alagbaoso, Manessah O. (University of the Witwatersrand, Johannesburg, 2008)
In the business environment of South African banking industry, informed and committed employees are a source of competitive advantage. More than ever before, organisations’ strategies need to be effectively communicated, understood at all levels, and effectively implemented. The purpose of this study is to examine factors responsible for the effective communication of strategy between the head office and the network of a South African banking organization using the face-to-face medium. The data for this study was collected via a questionnaire and statistically analysed using Descriptive Statistics, Factor Analysis, Cluster Analysis and Analysis of Variance (ANOVA). A five-factor solution was obtained and the factors are: 1. Interpersonal Communication; 2. Change and Improvement; 3. Employee Involvement in Strategy Formulation; 4. Stability; and 5. Vertical Communication. Of these five factors, the first three are deemed significantly important to strategy communication effectiveness and factors one and five are specifically important to effective strategy communication through the use of the face-to-face medium. The Cluster Analysis resulted in six clusters named: 1. Best of both worlds; 2. Specialists; 3. Elitists; 4. Bureaucrats; 5. Salesmen; and 6. Ostriches. The research confirmed the importance of the involvement of all levels of managers in strategy formulation and the predominant use of the face-to-face medium for effective strategy communication. Other key recommendations include the use of managers that have been in the organisation for more than six months and less than ten years for policies related to strategy communication, and the specific use of middle managers to oversee policies related to strategy communication using the face-to-face medium.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, 2008
Keywords: Strategy communication; South African banking industry; UCTD; SDG-8: Decent work and economic growth